2021
DOI: 10.1101/2021.08.26.457858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A thalamo-centric neural signature for restructuring negative self-beliefs

Abstract: Negative self-beliefs are a core feature of psychopathology. Despite this, we have a limited understanding of the brain mechanisms by which negative self-beliefs are cognitively restructured. Using a novel paradigm, we had participants use Socratic questioning techniques to restructure self-beliefs during ultra-high resolution 7-Tesla functional magnetic resonance imaging (UHF fMRI) scanning. Cognitive restructuring elicited prominent activation in a fronto-striato-thalamic circuit, including the mediodorsal t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…This result is consistent with past studies, including our own, that have reported significant MD involvement in tasks probing aspects of self-referential cognition (Araujo et al 2015;Davey et al 2016). Recently, in Steward et al (2021), we examined the MD's specific modulatory influence on distributed prefrontal regions, addressing the hypothesis that it has a key orchestrating influence on the activity of task-relevant higher cortical circuits (Parnaudeau et al 2018;Pergola et al 2018;Halassa and Sherman 2019;Wolff and Vann 2019). We used a task that evoked aspects of self-referential cognition and regulatory control and found the MD to have a robust excitatory influence on multiple PFC subregions, whilst receiving distinct reciprocal modulation from the MPFC.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This result is consistent with past studies, including our own, that have reported significant MD involvement in tasks probing aspects of self-referential cognition (Araujo et al 2015;Davey et al 2016). Recently, in Steward et al (2021), we examined the MD's specific modulatory influence on distributed prefrontal regions, addressing the hypothesis that it has a key orchestrating influence on the activity of task-relevant higher cortical circuits (Parnaudeau et al 2018;Pergola et al 2018;Halassa and Sherman 2019;Wolff and Vann 2019). We used a task that evoked aspects of self-referential cognition and regulatory control and found the MD to have a robust excitatory influence on multiple PFC subregions, whilst receiving distinct reciprocal modulation from the MPFC.…”
Section: Discussionsupporting
confidence: 93%
“…Both divisions were implicated as DMN hubs in the Alves et al (2019) study, whereas in a related study by Greene et al (2020), the MD was mapped more distinctly as a 'cognitive integration zone', linking the DMN to other large-scale cortical networks. Recent work by our group has complemented these findings by mapping a broad excitatory influence of the MD on multiple prefrontal regions, including the MPFC, during a cognitive self-regulation task (Steward et al 2021). Its results argue for a distinct coordinating role of the MD during higher cognition, whereby its task-evoked activity helps to sustain the engagement of cortical function.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations